The role of pyroptosis and its crosstalk with immune therapy in breast cancer - Wu, Ling; Lu, Hongsheng; Pan, Yin; Liu, Chen; Wang, Jinyan; Chen, Baofu; Wang, Yichao (Frontiers in Immunology, 2022)
Pyroptosis, a novel type of programmed cell death (PCD) mediated by multiple inflammasomes, can recognize several stimuli to pilot the cleavage of and activate inflammatory cytokines like IL-18 and IL-1β is believed to have dual effects on the development of multiple cancers including breast cancer. However, the effects of pyroptosis on cancer vary in distinct tissues and genetic backgrounds. Recently, the association between pyroptosis and breast cancer has received more and more attention, and the induction of pyroptosis in cancer is perceived as a potential strategy for cancer therapy. In addition, a great deal of evidence accumulating over the past decades has demonstrated that crosstalk between pyroptosis and cancer immunotherapy. Thus, a comprehensive summary combining the role of pyroptosis in breast cancer and antitumor immunity is imperative. In this review, we describe what is currently known regarding the multidimensional roles of pyroptosis in cancer, and focus on summarizing the mechanism of pyroptosis in breast cancer. Furthermore, we elucidate the impact of inflammasomes and pyroptosis-produced cytokines on the tumor microenvironment (TME) of breast cancer. Taken together, we aim to provide a clue to harness pyroptosis rationally and apply it to augment immunotherapy efficiency for breast cancer.